Real-life effects of dupilumab in patients with severe type 2 asthma, according to atopic trait and presence of chronic rhinosinusitis with nasal polyps - Pelaia, Corrado; Benfante, Alida; Busceti, Maria Teresa; Caiaffa, Maria Filomena; Campisi, Raffaele; Carpagnano, Giovanna Elisiana; Crimi, Nunzio; D’Amato, Maria; Foschino Barbaro, Maria Pia; Maglio, Angelantonio; Minenna, Elena; Nolasco, Santi; et al. (Frontiers in Immunology, 2023)
Background The efficacy of dupilumab as biological treatment of severe asthma and chronic rhinosinusitis with nasal polyps (CRSwNP) depends on its ability to inhibit the pathophysiologic mechanisms involved in type 2 inflammation. Objective To assess in a large sample of subjects with severe asthma, the therapeutic impact of dupilumab in real-life, with regard to positive or negative skin prick test (SPT) and CRSwNP presence or absence. Methods Clinical, functional, and laboratory parameters were measured at baseline and 24 weeks after the first dupilumab administration. Moreover, a comparative evaluation was carried out in relation to the presence or absence of SPT positivity and CRSwNP. Results Among the 127 recruited patients with severe asthma, 90 had positive SPT, while 78 reported CRSwNP. Compared with the 6 months preceding the first dupilumab injection, asthma exacerbations decreased from 4.0 (2.0-5.0) to 0.0 (0.0-0.0) (p < 0.0001), as well as the daily prednisone intake fell from 12.50 mg (0.00-25.00) to 0.00 mg (0.00-0.00) (p < 0.0001). In the same period, asthma control test (ACT) score increased from 14 (10-18) to 22 (20-24) (p < 0.0001), and sino-nasal outcome test (SNOT-22) score dropped from 55.84 ± 20.32 to 19.76 ± 12.76 (p < 0.0001). Moreover, we observed relevant increases in forced expiratory volume in one second (FEV1) from the baseline value of 2.13 L (1.62-2.81) to 2.39 L (1.89-3.06) (p < 0.0001). Fractional exhaled nitric oxide (FeNO) values decreased from 27.0 ppb (18.0-37.5) to 13.0 ppb (5.0-20.0) (p < 0.0001). These improvements were quite similar in subgroups of patients characterized by SPT negativity or positivity, and CRSwNP absence or presence. No statistically significant correlations were detected between serum IgE levels, baseline blood eosinophils or FeNO levels and dupilumab-induced changes, with the exception of FEV1 increase, which was shown to be positively correlated with FeNO values (r = 0.3147; p < 0.01). Conclusion Our results consolidate the strategic position of dupilumab in its role as an excellent therapeutic option currently available within the context of modern biological treatments of severe asthma and CRSwNP, frequently driven by type 2 airway inflammation.